Pengaruh Penerapan Kode Etik Akuntan Publik terhadap Kemampuan Auditor dalam Mendeteksi Fraud pada Perusahaan Asuransi: Suatu Kajian Literatur - Ariesyarti Setiadewi; Tiolina Evi Pardede (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to analyze the influence of the implementation of the public accountant code of ethics on auditors’ ability to detect accounting fraud in insurance companies using a Systematic Literature Review (SLR) approach. Fraud in financial statements is a serious issue that can reduce public trust in corporate financial information. In this context, auditors play an essential role in ensuring the fairness of financial statements through an independent and professional audit process. The implementation of the public accountant code of ethics, which includes the principles of integrity, objectivity, professional competence, and independence, is believed to contribute to improving audit quality and auditors’ ability to identify indications of fraud. This research employs the Systematic Literature Review method by examining relevant scientific articles from national and international journals published between 2015 to 2025. The literature selection process was conducted through stages of identification, screening, and analysis of studies related to professional ethics, auditors’ fraud detection ability, and audit quality. The results indicate that the implementation of the public accountant code of ethics has a positive influence on auditors’ ability to detect fraud through increased integrity, professional skepticism, and auditor independence. These findings provide theoretical contributions to the auditing literature and practical implications for the accounting profession in strengthening ethical compliance to improve audit effectiveness, particularly in the insurance industry.